Communication and Income Smoothing Through Accounting Method Choice - Suh, Yoon S. (Management Science, 1990)
This paper shows how accounting income smoothing could arise as rational equilibrium behavior. I develop a two-period agency model in which an agent obtains, after the first period's production operation, private information regarding future productivity of the operation. Direct communication of the agent's private signal yields a strict Pareto improvement over no-communication in this two-period world since it allows the agent to achieve signal-contingent interperiod consumption smoothing. Delegation of accounting method choice to the agent is shown to be an alternative, Pareto-equivalent mechanism to direct communication in this paper. Thus, accounting method choice is one way to achieve interperiod signal-contingent consumption smoothing by smoothing accounting income. One such accounting choice which arises from the structure of the problem is the choice of depreciation method.